1996
DOI: 10.1111/j.1532-5415.1996.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Clock Drawing Test Predict Cognitive Decline in Older Persons Independent of the Mini‐Mental State Examination?

Abstract: Findings suggest that the CDT identifies older persons at high risk of cognitive decline and adds prognostic information that supplements the standard MMSE test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 24 publications
1
60
0
10
Order By: Relevance
“…Similar to the results of other studies [13, 20, 26, 27, 28], we found that CDT-D had a slightly better sensitivity and specificity than the CDT-C in the screening of early dementia. When the CDT-D was administered, the subjects needed to initiate their thoughts and actions in preparation for a clock face drawing, for putting numerals in the proper position on the clock face and for drawing two hands of different lengths in the correct positions.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the results of other studies [13, 20, 26, 27, 28], we found that CDT-D had a slightly better sensitivity and specificity than the CDT-C in the screening of early dementia. When the CDT-D was administered, the subjects needed to initiate their thoughts and actions in preparation for a clock face drawing, for putting numerals in the proper position on the clock face and for drawing two hands of different lengths in the correct positions.…”
Section: Discussionsupporting
confidence: 81%
“…Several scoring systems have been used and standardized by investigators as a screen for cognitive dysfunction (27)(28)(29)(30). In this test, participants are presented with two sheets of paper: one provides written instructions, the other serves as a response sheet.…”
Section: Clock Drawing Testmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] In Brazil, however, only Okamoto 22 and Fuzikawa et al 23,24 have produced the few studies published about this instrument. Okamoto 22 studied spontaneous clock drawings, ability to tell time, placement of the hour hand, and copies of clock drawings in 50 patients with Alzheimer's dementia (DAT), nine with Lewy body dementia (DLB), six with mild cognitive impairment (MCI), and 43 from a control group.…”
Section: Introductionmentioning
confidence: 99%